Pete the Cat: Making New Friends - Dean, Kim, 1969-; Dean, James, 1957- (New York, NY : HarperCollins Canada, Limited, 2021)
"In Pete the Cat: Making New Friends, Secret Agent Meow, also known as Pete the Cat, is ready to crack the case! Join Pete and Squirrel as they go on a mission to make new friends. Pete the Cat: Making New Friends is a Level One I Can Read Comic, which means it will introduce children into the world of graphic novel storytelling and encourage visual literacy in emerging readers."--Publisher description.
Keywords: Cats -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Cats -- Fiction; Friendship -- Fiction; Readers (Publications); Comics (Graphic works)